Peningkatan Pengembangan Masyarakat Soya dalam Kekerabatan Kelompok (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
This community service program aimed to strengthen community development in Negeri Soya by reinforcing group kinship ties within a multicultural society. As a traditional village in Ambon City, Negeri Soya is inhabited by people from diverse ethnic and social backgrounds who live together in one area. This diversity requires harmonious social relations supported by solidarity, brotherhood, and social awareness. The program focused on the men’s service group of the Elim Sector, Soya Congregation, as a forum for social and spiritual development. The activities were conducted through lectures, question-and-answer sessions, and collaborative practices in church services. The materials emphasized group kinship, social solidarity, togetherness, and the understanding that kinship is not limited to blood relations, but can also be built through shared territory, life experiences, and continuous social interaction. The results show that the Negeri Soya community has strong solidarity and active participation in religious and social activities. Values such as mutual cooperation, masohi, and the concept of orang basudara serve as important foundations for social integration. Men’s church service activities strengthened care, cooperation, and shared responsibility among members. These findings indicate that local cultural values remain relevant for managing diversity and building collective resilience in post-conflict communities. Overall, this program contributed positively to strengthening social relations and supporting harmonious, inclusive, and sustainable community life in Negeri Soya in daily life.